Hepatocellular carcinoma in patients with chronic hepatitis C and cirrhosis in Denmark: A nationwide cohort study. Issue 1 (22nd September 2017) - Hallager, S.; Ladelund, S.; Kjær, M.; Madsen, L. G.; Belard, E.; Laursen, A. L.; Gerstoft, J.; Røge, B. T.; Grønbæk, K. E.; Krarup, H. B.; Christensen, P. B.; Weis, N.
Summary: Cirrhosis in patients with chronic hepatitis C increases the risk of hepatocellular carcinoma (HCC), and surveillance with ultrasound (US) and alpha‐fetoprotein (AFP) is recommended. This study aimed to estimate changes in the HCC incidence rate (IR) over time, HCC stage and prognosis, and AFP and US performed in patients with hepatitis C and cirrhosis. Eligible patients were identified in the Danish Database for Hepatitis B and C, and data from national health registries and patient charts were obtained. Tumour stage was based on Barcelona‐Clinic Liver Cancer stage, TNM classification and size and number of lesions combined into stages 0‐3. We included 1075 patients with hepatitis C and cirrhosis, free of HCC and liver transplant at baseline. During 4988 person years (PY), 115 HCC cases were diagnosed. The HCC incidence rate increased from 0.8/100 PY [CI95% 0.4‐1.5] in 2002‐2003 to 2.9/100 PY [2.4‐3.4] in 2012‐2013. One‐year cumulative incidence of at least one AFP or US was 53% among all patients. The positive predictive value of an AFP ≥ 20 ng mL −1 was 17%. Twenty‐three (21%) patients were diagnosed with early‐stage HCC (stage 0/1) and 84 (79%) with late stage. Median survival after HCC for early‐stage HCC disease was 30.1 months and 7.4 months for advanced HCC (stage 2/3). The incidence rate of HCC increased over time among patients with hepatitis C and cirrhosis in Denmark. Application of AFP and US was suboptimal, and most patients were diagnosed with advanced HCC with a poor prognosis.